Evaluating the programme and behavior change theories of a community alcohol education intervention in rural Sri Lanka: a study protocol - Jane Brandt Sørensen; K. S. Kylie Lee; Andrew Dawson; Angela Dawson; Lalith Senarathna; P. H. G. Janaka Pushpakumara; Thilini Rajapakse; Flemming Konradsen; Nick Glozier; Katherine M. Conigrave; Prabash Siriwardhana; David Hansen; et al. (Taylor & Francis Group, 2023)
Risky alcohol use is a major public health problem globally and in Sri Lanka. While a reduction in alcohol consumption can result in physical, mental, and social benefits, behaviour change is difficult to achieve. Effective, context-adapted interventions are required to minimise alcohol-related harm at a community level. THEATRE is a complex, community-based intervention evaluating whether a promising Sri Lankan pilot study that utilised arts-based research to moderate alcohol use can be scaled up. While the scaled-up pilot study protocol is presented elsewhere, the aim of this protocol paper is to describe the intervention programme theory and evaluation design, and modifications made to the study resulting from COVID-19 and the financial crisis. Drawing on the Behaviour Change Wheel (BCW) and Theoretical Domains Framework, behaviour change theories are presented with potential pathways to guide implementation and evaluation. Alcohol consumption patterns and context of drinking is detailed. The multifaceted intervention targets individuals and communities using arts-based interventions. Four of nine BCW functions are employed in the design of the intervention: education, persuasion, modelling and enablement, and training. Modifications made to the study due to COVID-19 and the financial crisis are described. Ethical approval was obtained from the Ethics Review Committee, Faculty of Medicine and Allied Sciences, Rajarata University of Sri Lanka (ERC/2018/21-July 2018 and Feb 2022) and the University of Sydney (2019/006). Findings will be disseminated locally to community members and key stakeholders and via international peer-reviewed publications.